2012
DOI: 10.1159/000342920
|View full text |Cite
|
Sign up to set email alerts
|

Side Effects of Anti-Thyroid Drugs and Their Impact on the Choice of Treatment for Thyrotoxicosis in Pregnancy

Abstract: Introduction: Hyperthyroidism in pregnancy is a serious condition and its management is complex. Whilst carbimazole/methimazole (CBZ/MMI) and propylthiouracil (PTU) have similar efficacies in controlling hyperthyroidism, their risk of side effects such as major congenital abnormalities and hepatotoxicity are different. Methods: Various combinations of the terms ‘anti-thyroid drugs’, ‘thionamide’, ‘carbimazole’, ‘methimazole’, ‘propylthiouracil’, ‘pregnancy’, ‘side effects’, ‘agranulocytosis’, ‘birth defects’, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(51 citation statements)
references
References 86 publications
1
45
0
5
Order By: Relevance
“…The vast majority of reported cases of birth defects after pregnancy exposure to ATDs have occurred after ATD therapy in the first trimester of pregnancy (9,15), which is the period of organogenesis as illustrated in Fig. 1 (12).…”
Section: Time Windows Of Relative Safety and High Riskmentioning
confidence: 99%
See 2 more Smart Citations
“…The vast majority of reported cases of birth defects after pregnancy exposure to ATDs have occurred after ATD therapy in the first trimester of pregnancy (9,15), which is the period of organogenesis as illustrated in Fig. 1 (12).…”
Section: Time Windows Of Relative Safety and High Riskmentioning
confidence: 99%
“…The dominating cause of hyperthyroidism in women of fertile age is Graves' disease (5), and antithyroid drug (ATD) therapy is commonly used to achieve euthyroidism and a gradual remission of the autoimmune aberration of Graves' disease (6). However, the ATD methimazole (MMI) and its prodrug carbimazole (CMZ) may have teratogenic effects (7,8,9,10,11), and recently it has been shown that children who have been exposed to propylthiouracil (PTU) during the period of organogenesis are also at an increased risk of having some specific birth defects (11). In general, major structural defects are observed in w3% of neonates (12) and additional birth defects are detected later.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the use of propylthiouracil is deemed necessary as untreated hyperthyroidism results in serious complications such as pregnancy-induced hypertension, thyroid storm, heart failure, premature labour, miscarriage and placental abruption. Other antithyroid medications such as carbimazole and methimazole had been associated with craniofacial malformations [28][29]. Therefore, the FDA, US still recommends propylthiouracil as the preferred antithyroid medication during the first trimester of pregnancy [28].…”
Section: Discussionmentioning
confidence: 99%
“…The risks include fetal goitre and transient hypothyroidism. 2,24 Both drugs can cause maternal agranulocytosis. 24 Propylthiouracil is recommended as the first-line antithyroid drug in the first trimester as carbimazole is associated with congenital abnormalities.…”
Section: Antithyroid Therapymentioning
confidence: 99%